CAUSES AND REMEDIES FOR NON-INFECTIOUS INFERTILITY IN SHEEP AND GOATS - Ömer Uçar; Baris Atalay Uslu (Universitas Syiah Kuala, 2021)
Non-infectious infertility is particularly critical for sire rams/bucks, as seasonal breeders. This seasonal heavy use of males may lead to sexual exhaustion such that the regular semen production, libido, ejaculation, and litter yield can be seriously impaired. In severe cases, the reproductive processes may stop completely. For avoiding infertility risk, management and feeding should firstly be arranged with a flock-based approach. In reproductive management, the issues of using teaser ram/buck, male/female ratio, weekly mating number, exercise, and experience need attention. Also, inbreeding and using old breeders should be avoided. In oestrus synchronisation, necessary precautions against extremely hot/arid climatic conditions should be considered together with a sufficient number of rams/bucks used rotationally. For sustainable sheep/goat breeding, protective-preventive measures are preferred to problem-solving approaches. In enterprises where female breeder welfare is a priority, sustainable individual yield increases. Further, only the comfort level of males used heavily in season allows the expected libido and fertility to occur. In small ruminants, the necessary interest and responsibility in production provide convenience in the ideal solution with the opportunity of early interventions against undesirable fertility problems in breeders. Undoubtedly, it is vital to consider sustainable animal health and welfare for profitable breeding and husbandry in sheep/goats.